Heidegger, Plato, philosophy, death an atmosphere of mortality - Rojcewicz, Richard (Lexington Books, 2021)
"Richard Rojcewicz argues that Heidegger and Plato see the same connection between philosophy and death: philosophizing is dying in the sense of separating oneself from the prison constituted by superficiality and hearsay. Rojcewicz relates this understanding of philosophy to signs, anxiety, conscience, music, and the COVID-19 pandemic"--